Analisis Prediksi Kebangkrutan Menggunakan Metode Altman Z-Score, Zmijewski, Springate dan Grover Pada PT Martina Berto Tbk Yang Terdaftar Di Bei Tahun 2018-2022 - Elya Yuliani; Usdeldi Usdeldi; Mohammad Orinaldi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the financial condition of companies that are facing financial difficulties at PT Martina Berto Tbk, which is a company in the cosmetics sub-sector. This research is a quantitative descriptive research. The data source in this research is secondary data in the form of annual company financial reports. This research uses a population of all financial reports of PT Martina Berto Tbk. This research aims to analyze the bankruptcy of PT Martina Berto Tbk which is listed on the IDX, usin g the Altman Z-Score, Zmejewski, Springate dan Grover methods, in the 2018-2022 financial statements, then analyze the bankruptcy of PT Martina Berto Tbk based on the bankruptcy criteria for each method. analysis, the results obtained were that PT Martina Berto Tbk was predicted to go bankrupt by two analysis methods, namely the Altman Z-Score, Springate, Grover methods. So it can be concluded that PT Martina Berto Tbk will go bankrupt in the future if it does not prepare steps and strategies to overcome bankruptcy.